Yield and Forage Value of a Dual‐Purpose bmr‐12 Sorghum Hybrid. Issue 2 (1st March 2015) - Yerka, Melinda K.; Watson, Andrea; Toy, J. J.; Erickson, Galen; Pedersen, Jeffrey F.; Mitchell, Rob
ABSTRACT: Grain sorghum [ Sorghum bicolor (L.) Moench] is an important crop for rainfed production systems with 2.7 million ha grown in the United States in 2013. The brown‐midrib ( bmr ) mutations, especially bmr‐12, have resulted in low stover lignin and high fiber digestibility without reducing grain yield in some sorghum lines. However, the effect of the bmr trait on beef cattle ( Bos taurus ) performance when grazing crop residue is unknown. Our objectives were to validate previous small‐plot results reporting no grain yield difference between near‐isogenic bmr‐12 (BMR) and wild‐type control (CON) A Wheatland × R Tx430 sorghum hybrids in a field‐scale experiment and to determine if BMR stover enhances beef production in a grazing experiment. Four replicated paddocks (2.3 ha) were planted in 2006 and 2008 near Mead, NE. Crossbred yearling steers (240 ± 17 kg hd −1 ) grazed (2.6 steers ha −1 ) paddocks following grain harvest for 72 d in 2006 and 61 d in 2008. Forage was sampled 4, 30, and 60 d after grazing began. Grain yield of BMR was 6% less ( P = 0.01) than CON with no difference in stover neutral detergent fiber (NDF) content, but BMR stover had higher in vitro NDF digestibility (IVNDFD) (31%; P < 0.0001), steer average daily gain (ADG; 0.18 kg hd −1 d −1 ; P = 0.001), and body weight (BW) gain (29 kg ha −1 ; P = 0.002), resulting in an estimated increase in net return of $133.84 ha −1 due to BMR. Results suggest that the A Wheatland × R Tx430 bmr‐12 hybrid is an effective dual‐purpose sorghum crop for both grain and beef production.